2020
DOI: 10.1177/0363546520935437
|View full text |Cite
|
Sign up to set email alerts
|

An In-Depth Analysis of Graft Rupture and Contralateral Anterior Cruciate Ligament Rupture Rates After Pediatric Anterior Cruciate Ligament Reconstruction

Abstract: Background: Reported rates of graft rupture and contralateral anterior cruciate ligament (ACL) rupture after ACL reconstruction (ACLR) are higher among pediatric patients than adults. Previous series may have underestimated postoperative event risk because of small sample sizes and high proportions of dropouts. Purpose: To calculate rates of graft rupture and contralateral ACL rupture after ACLR in a large pediatric series. Study Design: Case series; Level of evidence, 4. Methods: ACLRs performed in our tertia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…27,41 Some data demonstrate that in an active, young population, the contralateral injury risk is not only similar, but may be even greater than the index surgical side. 45 In contrast, in the study by DeFrancesco et al, 43 there was a 4-year cumulative rate of contralateral ACL rupture of 15.7% and 8.1% in those with transphyseal reconstructions <16 and !16 years, respectively, which is lower than their ipsilateral graft rupture rates. There were no significant differences identified in contralateral ACLR in our cohort, and Cordasco et al 34 also did not find a difference in contralateral ACLRs comparing their all-epiphyseal, partial or complete transphyseal, and boneepatellar tendonebone autograft groups.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…27,41 Some data demonstrate that in an active, young population, the contralateral injury risk is not only similar, but may be even greater than the index surgical side. 45 In contrast, in the study by DeFrancesco et al, 43 there was a 4-year cumulative rate of contralateral ACL rupture of 15.7% and 8.1% in those with transphyseal reconstructions <16 and !16 years, respectively, which is lower than their ipsilateral graft rupture rates. There were no significant differences identified in contralateral ACLR in our cohort, and Cordasco et al 34 also did not find a difference in contralateral ACLRs comparing their all-epiphyseal, partial or complete transphyseal, and boneepatellar tendonebone autograft groups.…”
Section: Discussionmentioning
confidence: 85%
“…A large case series by DeFrancesco et al. 43 including 504 transphyseal surgeries in patients <16 years and 331 patients ≥16 years found graft rupture rates in these 2 groups of 21.6% and 16.4%, respectively. There is less data currently available on the partial or hybrid transphyseal technique available on reinjury rates; one prospective evaluation by Cordasco et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve of the included articles [185][186][187][188][189][190][191][192][193][194][195][196] were not eligible for meta-analysis (e.g., only one study assessing the specific risk factor or reported statistics not possible to calculate as odds ratios). individual study included in the meta-analyses).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Autograft ACL reconstruction has significantly lower rates of graft failure as compared to allograft. [47][48][49] Double-bundle or single-bundle PCL reconstruction, posterolateral corner, and posteromedial corner reconstructions can be performed with allograft in the adolescent patient population with acceptable outcomes. 6,50 PCL reconstruction is performed for those injuries with significant instability despite initial conservative management.…”
Section: Neuropraxiamentioning
confidence: 99%